2021
DOI: 10.1177/2325967121993179
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Measurements in the Assessment of Patellar Instability: A Systematic Review and Meta-analysis

Abstract: Background: Numerous diagnostic imaging measurements related to patellar instability have been evaluated in the literature; however, little has been done to compare these findings across multiple studies. Purpose: To review the different imaging measurements used to evaluate patellar instability and to assess the prevalence of each measure and its utility in predicting instability. We focused on reliability across imaging modalities and between patients with and without patellar instability. Study Design: Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 119 publications
(242 reference statements)
1
29
0
Order By: Relevance
“…This study may partially explain why there is no significant difference in TT-PCL distance between patients with patellar instability and healthy individuals, as a recent systematic review showed. 29 Individualized measurements of the TT-TG distance were also proposed for diagnosing a lateralized TT in patients with recurrent patellar dislocation. 15 , 17 , 21 , 22 TT-RA is not affected by individual tibial size; therefore, the individual variability of pathologic values may be minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study may partially explain why there is no significant difference in TT-PCL distance between patients with patellar instability and healthy individuals, as a recent systematic review showed. 29 Individualized measurements of the TT-TG distance were also proposed for diagnosing a lateralized TT in patients with recurrent patellar dislocation. 15 , 17 , 21 , 22 TT-RA is not affected by individual tibial size; therefore, the individual variability of pathologic values may be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…The tibial tuberosity (TT)–trochlear groove (TT-TG) distance is commonly used for the assessment of TT lateralization (TTL) in patients with patellar dislocation. 9 , 12 , 18 , 29 However, recent studies have suggested that the TT-TG distance is affected by several factors, such as knee rotation, femoral anteversion, and trochlear groove medialization (TGM), rather than TTL alone. 1 , 3 , 7 , 16 , 23 , 30 In addition, it is difficult to measure the TT-TG distance in patients with trochlear dysplasia because the deepest point of the trochlea is unclear in these patients.…”
mentioning
confidence: 99%
“…31 The ideal imaging modality for each measurement is unknown, and the utility of originally described cutoff values across imaging modalities has not been validated. 13,36 On MRI scans, measurements utilizing bony versus cartilaginous landmarks are often performed interchangeably, despite evidence that they may differ in the evaluation of trochlear dysplasia. 33 Trochlear dysplasia has been more commonly reported in female patients, suggesting that increased anatomic risk factors may account for sex-specific differences in patellar instability.…”
Section: -In-5mentioning
confidence: 99%
“…Assessment of patellofemoral congruence is performed in routine practice in cases of patellofemoral instability [ 1 , 2 ], painful patellar syndrome [ 3 ], or patellofemoral osteoarthritis [ 4 ]. In these cases, the analysis of patellofemoral congruence makes it possible to justify a surgical treatment choice in case of chronic instability or chronic patellofemoral pain (tibial tuberosity osteotomy, external patellar release, axial correction and/or derotation osteotomy, medial patellofemoral ligament reconstruction) [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However in 2013, a meta-analysis demonstrated that there was insufficient evidence to determine the reliability, validity, sensitivity, and specificity of this congruence angle [ 12 ]. In fact, the various studies found were conducted either on a population with healthy knees, representative of only 20% of the general population, or on series of cases of patellofemoral instability, with great variability in the radiographic acquisition protocols [ 2 ]. Moreover, no intraobserver or intraobserver analysis was performed of this radiographic measurement according to the level of trochlear or patellar dysplasia.…”
Section: Introductionmentioning
confidence: 99%